From Control to Coexistence: Reframing Integrated Pest Management under Climate and Environmental Change - Qalbin Salim Fazli; Haikal Azis; Mussa Isaack Delya; Erick Hironimus Kihwili; Ghalieb Mutig Idroes; Ghazi Mauer Idroes (Leuser Journal of Environmental Studies, 2026)
This study examines the evolution of research on integrated pest management (IPM) in relation to climate change and environmental impacts through a bibliometric analysis of Scopus-indexed publications from 2003 to 2026. By integrating publication trends, collaboration networks, keyword co-occurrence, and conceptual structure mapping, the study identifies a significant post-2019 expansion reflecting increasing global urgency toward sustainable agriculture. The findings reveal a structural shift from pesticide-dependent approaches to ecologically based and climate-adaptive strategies, with growing integration of biodiversity, ecosystem services, and agroecology within IPM frameworks. Conceptual analysis further indicates that IPM functions as a transitional bridge between conventional and sustainability-oriented paradigms. Despite expanding international collaboration, research contributions remain geographically concentrated, highlighting a mismatch between knowledge production and vulnerability to climate-driven pest risks. The study underscores an ongoing paradigm transition and emphasizes the need for inclusive, context-specific, and climate-resilient IPM strategies.